The Technology of Producing Biohumus and the Study of its Qualitative Indicators - Gneush, Anna; Zholobova, Inna; Petenko, Alexander; Gorkovenko, Natalia; Yurina , Natalia (KnE Life Sciences, 2021)
This article presents the results from the development of a technology for producing biohumus from the feces of cattle and winter wheat straw in a biodynamic fermenter. Nitrifying agents are important for soil fertility, which is dependent on the intensity of the nitrification process. This group includes aerobic cellulose-destroying microorganisms, denitrifiers and sulfate-reducing bacteria. The ratio of these groups and their composition are changing. Therefore, the study of the quantitative ratio of microbial communities involved in the formation of biohumus was of considerable scientific interest. During the microbiological analyses, a large number of microorganisms were found to be involved in the decomposition of the organic compounds. Aminoautotrophic microorganisms represented the largest physiological group of microorganisms in the biohumus. The chemical composition of the biohumus was determined during the study and a sanitary microbiological analysis was performed. The content of gross forms of elements in the humic extract was also examined. The humic extract from the biohumus was a brown liquid with 15 g / l of humic acids, 5.0 g / l of fulvic acids, and gross forms of elements (potassium, phosphorus, nitrogen). The dry matter in the biohumus was 1.0% of the total composition and contained 0.1% nitrogen, 0.03% phosphorus P2O5 and 0.01% potassium K2O. It was found that high-quality organic fertilizer can be obtained using this technology. Keywords: biohumus, humic extract, chemical composition, sanitary-microbiological analysis, organic fertilizer